SEJARAH GLOBAL SEBAGAI PENDEKATAN BARU DALAM SEJARAH INDONESIA - Frial Ramadhan Supratman (IAIN Syekh Nurjati Cirebon, 2022)
History science should not be separated from thedevelopment of world philosophical thought. As a science, history isstill survived and used by many scholars until now. It proves thathistory is still relevant to solve problems in our life. Since thenineteenth century, history science is excessively influenced by theEurocentric view that it had been used to legitimate the power ofEuropean imperialism and colonialism in many colonies, likeNetherlands Indies, British Malaya, India, and so forth. Many scholarsfrom social humanities fields, such as Syed Hussein Alatas andEdward Said, have criticized the Eurocentric view in socialhumanities scholarships. Lately, historians have been using a newapproach that emphasizes global history. Global history writingsdiscuss problems on a larger scale to reduce the Eurocentric view inhistory science. It has been written and discussed by scholars inEurope, North America, and East Asia for several times ago.However, the global history approach has not been used yet as anapproach by academic or public historians in Indonesia. This articleexplores global history as an approach to historical methodology. Inthis article, the author uses historical literature that has been usingglobal history as an approach. The author argues that the globalhistory approach should be explored further to reduce the Eurocentricview in historical writings.